Principles and methods of rock support for rockburst control - Li, Charlie Chunlin (Journal of Rock Mechanics and Geotechnical Engineering, 2021)
This paper presents the principles of rock support for rockburst control and three rockburst support systems used in deep metal mines. Before the principles of rock support are presented, rock fracture related to strain burst is first discussed with the help of photos taken on site, and the energy sources and transformations during bursting are illustrated through conceptual models. Surface parallel extension fracture usually occurs in the ejected and surrounding rocks in a strain burst event, while the ejected rock in a fault-slip rockburst is often already pre-fractured before the event. There must be excessive release energy available for rock ejection. The excessive release energy comes from both the ejected rock itself and the surrounding rock. To prevent rock ejection in a rockburst, the support system must be able to dissipate the excessive release energy. All support devices in a support system for rockburst control must be able to dissipate energy, be firmly linked, and be compatible in deformability. A support system for rockburst control comprises surface-retaining devices and yield rockbolts as well as yield cablebolts when needed. Laying mesh on the top of shotcrete liner is a good practice to enhance the surface-retaining capacity of the support system. Energy-absorbing yield rockbolts dissipate energy either by stretching of the bolt shank or by sliding of the inner anchor in the borehole. Mesh, mesh strap and shotcrete are the surface-retaining devices widely used in the current rock support systems. The three types of rock support used for rockburst control at present are soft support system using Split Set bolts, hybrid support system using rebar and two-point anchored yield bolts, and entirely yieldable support system using strong yield bolts.